Practicing the Story: Equiping Congregations for Evangelism. (July 2016) - Lewis, Tracey
Abstract: "Evangelism" carries a lot of baggage! And many in our 21st‐century church feel that the baggage was packed by someone else and contains clothes that no longer fit or equip them for sharing the gospel with people and life in the present world. If evangelism is to find its place high on the agenda of our church of today, we need to enable Christian people to freely and honestly explore first, what it means to be people of the gospel now, and then, the message they have to share and how they will share it with the world today. Radical questions about our understandings of the gospel and purpose and practice in sharing it need to be asked, discussed, and explored with faith and courage in the many different contexts that Christian people are called to live and serve in. If the Christian church is to be faithful to the gospel and recognizing and growing the kingdom of God, then we must be listening to the discomfort within ourselves and our neighbours and open to the possibility of transformation. Can our Christian story, always a renewal movement, inspire that new thinking, sharing, and action that will reach the people we meet today?